Biochemical and haematological profiles of black Bengal goat in Mymensingh sadar of Bangladesh (Research in Agriculture Livestock and Fisheries, 2022)
The aim of the present study was to know the normal haemato- biochemical profiles of black Bengal goats in Bangladesh. Blood samples were collected from Jugular vein of 20 Black Bengal goats which were divided into 5 groups (4 goats in each group) on the basis of age, sex, nutritional and feeding status. The whole blood was analyzed for hematology, plasma and serum samples for biochemical analysis. The results of the present study demonstrate the normal haemato-biochemical values of the Black Bengal goat breeds with their age specificity. Total RBC (15.15 ± 1.29 million/cumm), haemoglobin (7.04 ± 1.02 g/dl), total WBC (11.64 ± 1.12), differential leukocyte counts of neutrophils (70.89 ± 2.06%), lymphocyte (23.79 ± 1.69%), eosinophil 2.1%), basophil (2.3%), MCV (35.04 ± 0.47) and PCV (26.98 ± 1.49%). This study also reveals the normal bio-logical profile counts as total protein (69.47±2.31 g/L), Albumin (42.47 ± 2.31g/L), Globulin (27.32g/L), Phosphorus (3.46 ± 1.19), blood Urea (22.97 ± 0.58), Creatinine (0.645mg/dl), ALT (20.32U/L), ALP (91.59 U/L), GGT (37.46 U/L), IgG (18.91 ± 1.14 g/L), IgM ( 2.87 ± 0.18g/L), gA (.031 ± 0.12g/L) and IL-6 (1.69±0.15g/ml). The study found higher number of RBC (million/cumm), WBC (Thousands/cumm), and PCV% in the goats of age 3 years and above (18.02 ± 1.27, 14.72 ± 1.19, and 28 ± 3.2), respectively. Besides, Neutrophils% and total protein was found higher (76.289 ± 14.5%, 77.52 ± 8.43 g/L), respectively in the Black Bengal goats of 6 months to 1 year age. Present results stated some significant variation of parameters between goats of various ages; on the other hand, some shows no significant variation at all.Res. Agric., Livest. Fish.8(3): 329-337, December 2021